Regulatory Harmonization and Agricultural Trade Barriers under IA-CEPA - Siti Khairunnissa; Ramalinggam Rajamanickman (Acta Law Journal, 2026)
The Indonesia–Australia Comprehensive Economic Partnership Agreement (IA-CEPA) establishes a comprehensive legal framework intended to promote bilateral trade liberalization and regulatory cooperation between Indonesia and Australia in the agricultural sector. Despite significant tariff reduction commitments, agricultural trade between Indonesia and Australia continues to encounter substantial barriers arising from differences in domestic legal system including sanitary and phytosanitary (SPS) measures, technical standards, import licensing systems, and biosecurity regulations. While previous studies have predominantly examined IA-CEPA from economic and trade perspectives, limited attention has been addressed to the normative legal harmonization between the domestic legal frameworks of both countries in implementing the Agreement. This study examines the regulation of agricultural tariff barriers under IA-CEPA from the perspective of international trade law principles and analyzes the harmonization of Indonesian and Australian national laws in implementing agricultural trade policies under the agreement. This study addresses that gap by providing a normative legal analysis of the consistency between IA-CEPA obligations and the agricultural trade regulations of Indonesia and Australia. This research employs a normative juridical method using statutory, treaty, conceptual, and comparative approaches through the examination of IA-CEPA provisions, WTO Agreements, Indonesian agricultural trade legislation, and Australian biosecurity laws. The findings reveal that IA-CEPA incorporates the fundamental principles of international trade law, including transparency, non-discrimination, proportionality, regulatory coherence, and market access. However, the implementation of these principles remains constrained by conflicting domestic regulatory priorities. Indonesia maintains protective agricultural policies aimed at preserving food sovereignty, farmer protection, and domestic market stability, whereas Australia emphasizes strict biosecurity governance and SPS compliance requirements to protect public health and environmental security. Consequently, domestic regulatory measures rather than tariff commitments continue to constitute the principal barriers to bilateral agricultural trade. The study further demonstrates that legal harmonization under IA-CEPA remains only partially achieved due to regulatory inconsistencies, overlapping administrative requirements, and differing regulatory philosophies. The novelty of this research lies in its normative assessment of regulatory harmonization between international treaty obligations and domestic agricultural trade laws, offering a legal framework for evaluating the effectiveness of bilateral trade agreements in balancing trade liberalization with state regulatory autonomy. The study contributes to international trade law scholarship by proposing a normative framework for assessing regulatory harmonization between bilateral trade agreements and domestic agricultural regulations.